2014
DOI: 10.1002/joc.4017
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the subtropical anticyclones over North Africa and Arabian Peninsula on the African easterly jet

Abstract: North African climate is analysed between 1979 and 2010 with an emphasis on August using the European Center for Medium‐Range Weather Forecast (ECMWF) global dataset to investigate the effects of the subtropical anticyclones over North Africa and the Arabian Peninsula on the African easterly jet (AEJ). It was found that the AEJ encloses a core with a local wind maximum (LWM) in both West and East Africa, in which the west LWM core has a higher zonal wind speed. The strength of both cores is distinctly differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 24 publications
2
19
0
Order By: Relevance
“…Climatologically, the model reproduces the spatial and behavioral patterns of the three cores of the AEJ (the eastern, central and western cores Figure 6c); though, with slight deviation in the positions and strength. These findings are similar to those of Grist and Nicholson (2001), Afiesimama (2007), and Spinks et al (2015). These imply that, irrespective of the ENSO phase considered and apart from wind directions, the ECMWF-S2S model poorly reproduce the wind strength that could depict AEJ at the 700 hPa level.…”
Section: African Easterly Jet (Aej)supporting
confidence: 73%
“…Climatologically, the model reproduces the spatial and behavioral patterns of the three cores of the AEJ (the eastern, central and western cores Figure 6c); though, with slight deviation in the positions and strength. These findings are similar to those of Grist and Nicholson (2001), Afiesimama (2007), and Spinks et al (2015). These imply that, irrespective of the ENSO phase considered and apart from wind directions, the ECMWF-S2S model poorly reproduce the wind strength that could depict AEJ at the 700 hPa level.…”
Section: African Easterly Jet (Aej)supporting
confidence: 73%
“…It was demonstrated in Spinks et al (2014) that the LWMs were reproduced in other data sets such as ECMWF 40-year reanalysis (ERA-40) at 2.5 ∘ (Uppala et al, 2005), the National Centre of Environmental Prediction (NCEP) reanalysis at 2.5 ∘ (Kalnay et al, 1996), and the Climate Forecasting System Reanalysis version 1 (CFSR) at 0.3 ∘ (Saha et al, 2006). Over the years, climatological analyses of the AEJ were carried out using global model data with relatively low spatial resolutions.…”
Section: The Datamentioning
confidence: 89%
“…It was shown that the divergent centre was formed from east-west differential heating by thermal low heating (hot) and downward (cold) branch of the Indian Monsoon. Similar procedure was performed by Spinks et al (2014) for the Arabian High. With the usage of a higher spatial resolution data set, two divergent centres were found respectively for the Saharan and Arabian Highs.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations